Impacts of endogenous opioid blockade and sex on working memory among ad-libitum and abstinent smokers and non-smokers - Ryan Johnson; Briana N. DeAngelis; Motohiro Nakajima; Sharon S. Allen; Mustafa al'Absi (Addiction Neuroscience)
Background: Research examining the effects of opioid receptor antagonists on working memory is limited by small sample sizes that are often comprised of only male participants. Moreover, they have yielded mixed findings, and no studies have examined such effects in the context of chronic nicotine use and temporary nicotine withdrawal. Methods: Male and female participants completed two lab visits at which they were administered either 50 mg naltrexone or an identical placebo (one at each lab using double-blind, counterbalanced administration). After a medication absorption period, performance on a mental arithmetic (working memory) task was assessed by number of correct responses, errors, and number of attempts. Participants were either non-smokers or regular smokers who were randomly assigned to use nicotine ad-libitum or to abstain from nicotine for 24 h prior to both lab visits. Results: The results indicate a significant main effect of opioid blockade on number of correct answers and accuracy rate during the mental arithmetic task, with poorer performance after opioid blockade compared to placebo. In addition, compared to male participants, female participants made fewer answer attempts, had fewer correct answers, and a lower accuracy rate. We did not find evidence of any differences based on smoking group (non-smoker, smoking abstinence, or ad-libitum smoking), nor were there any significant interaction effects. Conclusions: The findings suggest a modulating role of the endogenous opioid system in working memory function. Further investigation is needed to help identify the underlying mechanisms explaining the effects of the endogenous opioid system on working memory.